A relação entre compreensão leitora e consciência textual : um estudo com alunos de 2º e 3º anos do ensino fundamental - Barboza, Letícia da Silva (2014)
This study is inserted in the area of Psycholinguistics. Its goal is to verify the relationship between the textual awareness and reading comprehension. The survey includes 30 children, students of 2nd and 3rd grade of elementary school, from a public school in the metropolitan region of Porto Alegre. The performance of reading comprehension is evaluated through a questionnaire with eight questions relating to a story read by the subjects. The textual awareness development is verified by two instruments involving pictures. The participants need to remove the ones that do not belong to the story and then they have to organize the story s pictures according to the narrative sequence, justifying respectively. The research instruments are applied at two different moments, alternating the order of presentation for the subjects. First, after reading the narrative story, the subjects answer the questions about the text and then they do the textual awareness tasks. In another meeting, the subjects perform the tasks of textual awareness and after answering comprehension questions based on another narrative. In this study, the evidence of environment literacy in the family context is considered. This variable is checked by individual interviews with the participants. Also the schooling of the subjects is analyzed. The results for both groups indicate that subjects with better performance on the instrument reading comprehension also presents a significant degree of awareness of textual development , resulting in a positive correlation.